A Website Using Lean UX and Agile as a Promotional and Informational Media Platform (Case Study: Warkop Ahai, Kutacane City) - Buhqori Ramadhan; Cut Jupita Sari; Indah Kumalasari (STMIK Methodist Binjai, 2026)
Warkop Ahai is a coffee shop known in Kutacane for its traditional brewed coffee, local identity, and social function as a community meeting place. However, structured digital information regarding its products, business story, strengths, and location orientation is not yet available in a concise medium. This study aims to develop a promotional and informational website prototype for Warkop Ahai by integrating Lean UX and Agile. Requirements data were collected from open sources consisting of ten visible public reviews on a place aggregator, online media profiles, and relevant literature. The Lean UX stages comprised assumption declaration, minimum viable product creation, experiment, and learning, while Agile was implemented through Sprint 0 to Sprint 3. Multi-label analysis showed that taste and quality appeared in eight reviews, local or legendary identity in four, access or visit recommendation in two, service or cleanliness in two, and social function in one. The resulting product is a responsive static prototype containing home, strengths, menu, story, and location/contact sections. Structural and navigation testing across twelve scenarios produced twelve passed results. The study indicates that Lean UX and Agile integration can produce a rapid, measurable, and easily iterated minimum promotional medium. Nevertheless, user validation, prices, operating hours, contact details, and business information must be directly confirmed with the owner before the website is published as an official channel.